Pemberdayaan Ekonomi Keluarga dan Kesehatan pada Program Kampung Keluarga Berkualitas Desa Teras: Pemberdayaan Ekonomi Keluarga dan Kesehatan - Fara Fitriyani (Jurnal Pengabdian Masyarakat Manage, 2023)
KB villages were formed to improve the quality of human life at the village level or equivalent through the population, family planning and family development programs (KKBPK) as well as the development of related sectors in the framework of creating quality small families. Quality Family Village is an effort to make the KKBPK program a program that is organized from, by, and for the community. The purpose of this activity is to provide assistance and foster the community to organize quality family programs and increase public awareness regarding population-oriented development. Activities carried out in Teras Village with implementation methods including the pre-activity stage, the preparation stage, the implementation stage, and the evaluation stage. The results of the service activities are Quality Family Village Program Campaign, Posyandu Assistance, Stunting Prevention Campaign, and Family Economic Empowerment Activities. Evaluation of activities is carried out to see the sustainability of the mentoring process for the formation of Quality Family Villages in Teras Village